Multiple Commitment with the work and its influences on performance: a study among teachers of higher education in Brazil - Rowe, Diva Ester Okazaki; Bastos, Antonio Virgílio Bittencourt; Pinho, Ana Paula Moreno (Organizações & Sociedade, 2013)
This research analyzes, in teachers of higher education, the effects of links with thecareer (commitment and entrenchment) and with the Organization (commitment)in its performance. This is a cross-sectional research, involving a survey on line,whose questionnaire contained the previously validated scales for measuring thelinkages with the work. To evaluate teacher performance, two indicators were used:self-evaluation of his instructional effort and a measure of academic production. Thesample included 635 teachers of public and private institutions of higher education.The data were submitted to descriptive and multivariate analyses. To identify the impacts of links with the work on performance estimation method was used by partialleast squares (partial least squares-PLS). In the models tested, the entrenchment oncareer and organizational commitment instrumental influence negatively the academicproduction of the teachers and the commitment to career influences positivelythe instructional effort. The results show relevant evidence as the working link is animportant predictor of performance.